“How Do Students’ Perceptions of Green Finance and Artificial Intelligence Influence the Value of Sustainable Companies in Palembang?" - Akbar Sulbahri, Rifani; Pratama Putra, Dimas (Journal of Management, 2024)
This study aims to analyse how students' perceptions of green finance and artificial intelligence (AI) influence their attitudes towards sustainable corporate values in Palembang City. Using multiple regression analysis on questionnaire data from 250 students, findings indicate that positive perceptions of green finance (β = 0.45, p < 0.01) and AI (β = 0.38, p < 0.05) significantly impact students' support for sustainable corporate values. This study strengthens the understanding of how young generations perceive sustainability and technology in determining corporate values. Furthermore, this research highlights the need for further education on sustainable investment and AI implementation in business to enhance future generations' awareness of corporate sustainability.